KETERKAITAN ANTARA POLITIK PENDIDIKAN, KEBIJAKAN PENDIDIKAN DAN KEKUASAAN SERTA IMPLIKASINYA PADA PRAKTEK PENDIDIKAN DI LEMBAGA PENDIDIKAN (ISLAM): KETERKAITAN ANTARA POLITIK PENDIDIKAN, KEBIJAKAN PENDIDIKAN DAN KEKUASAAN SERTA IMPLIKASINYA PADA PRAKTEK PENDIDIKAN DI LEMBAGA PENDIDIKAN (ISLAM) - Damanhrui; Shodikin; Yacub, Jamiluddin; Permatasari, Ermanita; Kholijah, Siti (LPPM STAI Darussalam Lampung, 2024)
Islamic educational institutions spread throughout the country have become an important concern in the context of politics and power in Indonesia. This article aims to investigate how Islamic education and politics and power influence each other in Indonesia. The discussion in the article covers topics such as politics playing a role in Islamic educational institutions, the relationship between politics, power and Islamic education in Indonesia, the significance of political elements in Islamic education, and the role played by Islamic education in this country. The article will also discuss a number of related issues, such as the role of education in the realm of politics and power, the situation of Islamic education in Indonesia, educational patterns in Indonesia, and four issues that are closely related to the implementation of education based on power, including the process of domestication and misunderstanding, indoctrination, democracy in education, as well as social integration.